Fibre characteristics and enzyme levels of arm and leg muscles in elite cross-country skiers - Mygind, E. (Scandinavian Journal of Medicine & Science in Sports, 1995)
Performance tests and measurements of maximal aerobic capacity were performed during the competition period in elite cross-country skiers. Muscle biopsies were taken in the middle of January. Histochemical fibre typing, determination of fibre areas and number of capillaries as well as assays for citrate synthetase (CS), 3-hydroxyacyl coenzyme A dehydrogenase (HAD), lactate dehydrogenase (LDHtot and LDH1-2) were performed on biopsies from the triceps brachii (TRI) and vastus lateralis muscles (VAS). The relative percentage of slow-twitch fibres was 51.3 and 68.6 in TRI and VAS, respectively. The FTa fibre area in TRI was significantly larger than in VAS. No differences were found in the number of capillaries per fibre in TRI (2.7) and VAS (2.5). The number of capillaries per area was significantly lower in TRI (373) as compared to VAS (422). The LDHtot enzyme level was significantly higher in TRI than VAS, while the oxidative enzyme activities (CS and HAD) were significantly lower in TRI as compared with VAS. From all independent variables, only the maximal aerobic power was related significantly to performance time. The difference in maximal aerobic power between the skiers could explain 45% of the total variance in performance.